2021
DOI: 10.3390/su132212574
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Membranes in Protective Face Masks and Comparison of Reusable and Disposable Face Masks with Life Cycle Assessment

Abstract: In the COVID-19 pandemic period, the role of face masks is critical as a protective physical barrier to prevent droplets and filtrate exhalations coming from infected subjects or against various environmental threats, including the SARS-Cov-2 virus. However, the plastic and microplastic waste from the used face masks pollute the environment, cause a negative impact on human health and the natural ecosystem, as well as increase landfill and medical waste. The presented paper focuses on providing an overview of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…It requires less data input to obtain a preliminary evaluation of the environmental impact of materials and processes [ 29 ]. On the contrary, LCA is a complex and onerous procedure that requires the knowledge of extensive data to evaluate the full process from extraction of raw material to disposal [ 30 ]. Scheme 1 represents the system boundary considered in this work.…”
Section: Methodsmentioning
confidence: 99%
“…It requires less data input to obtain a preliminary evaluation of the environmental impact of materials and processes [ 29 ]. On the contrary, LCA is a complex and onerous procedure that requires the knowledge of extensive data to evaluate the full process from extraction of raw material to disposal [ 30 ]. Scheme 1 represents the system boundary considered in this work.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis on betacoronavirus (including SARS-CoV-2) concluded that while masks are generally effective in preventing virus transmission, respirators such as N95 are more protective than disposable medical masks or reusable multilayer (12-16-layer) cotton masks ( Chu et al, 2020 ). Similarly, Do Thi et al (2021) noted that reusable/washable (cloth) masks and disposable masks (both surgical masks and respirators) did help control the spread of SARS-CoV-2, although the highest protection was provided by respirators, followed by surgical masks, and finally cloth masks. Ho et al (2020) concluded, based on experiments with cotton versus medical masks worn by respiratory infected persons, that cotton masks could be a potential substitute for medical masks in air-conditioned micro environments and, given their washable and reusable nature, could be used by healthy individuals in community settings.…”
Section: Methodsmentioning
confidence: 96%
“…Previous studies have confirmed that cotton masks can offer protection against certain bacteria or viruses ( Chughtai et al, 2020 ; Ho et al, 2020 ), as well as reduce aerosol exposure ( Davies et al, 2013 ). The filtration capacity of these masks varies from 50% to 90% ( Do Thi et al, 2021 ), depending on the closeness of the gauze/cloth threads, the number of gauze/cloth layers, and the type of gauze/cloth ( Chughtai et al, 2013 ). While most cotton masks on the market are still not as effective as disposable products (e.g., medical masks) in terms of filtration, they can be reused after washing and maintain the desired protective performance over a certain number of washes if designed properly and used correctly ( Chughtai et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations